A poesia dos Metafísicos : modos da expressão e o efeito de "awareness" : I - wit - Lima, José Luís Araújo (1984)
In this first of a series of articles on the same subject, the focus is on Wit. Some critical attitudes towards Wit, either as a textual, function or as a reading effect, are considered to be of particular importance. The author refers to some seventeenth and twentieth century poems, thereby suggesting that a proper use of Wit may, through the ambiguity, complexity or extent of a poetical statement, lead one from the act of reading to a moment of awareness.